Фильтрующий материал и способ его получения - Волокитин Г. Г. Геннадий Георгиевич; Малиновская Т. Д. Татьяна Дмитриевна; Лысак И. А. Илья Александрович; Лысак Г. В. Галина Владиленовна; Лукашевич О. Д. Ольга Дмитриевна
опубл. 10.01.11